2005
DOI: 10.1007/s11258-004-5088-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Local Species Richness and Species Pool: A Case Study from the High Mountains of the Greater Caucasus

Abstract: The causes of linear relationships between local species richness and the size of the actual species pool in closed subalpine meadow communities and open plant communities of the alpine stony substrate (the Greater Caucasus Mountains) were analyzed using a computer simulation model. The results demonstrated that this relationship is insufficient evidence for the variation of local species richness among communities is wholly or partly determined by regional processes (the species-pool hypothesis). A relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Study scale is an important factor that drives relationships between local a-diversity and species pool (Koleff and Gaston 2002;Dufour et al 2006) and thereby the small area of springs might deepen the competitive exclusion and might be therefore responsible for our result. Our result supports the view that inherent linear or curvilinear relationships between local a-diversity and the size of regional species pool (Fox and Srivastava 2006) might not be always manifested (Akatov et al 2005). Our study demonstrates the different pattern of vascular plants and bryophyte species richness along environmental gradients in particular regions.…”
Section: Determinants Of A-diversitysupporting
confidence: 88%
“…Study scale is an important factor that drives relationships between local a-diversity and species pool (Koleff and Gaston 2002;Dufour et al 2006) and thereby the small area of springs might deepen the competitive exclusion and might be therefore responsible for our result. Our result supports the view that inherent linear or curvilinear relationships between local a-diversity and the size of regional species pool (Fox and Srivastava 2006) might not be always manifested (Akatov et al 2005). Our study demonstrates the different pattern of vascular plants and bryophyte species richness along environmental gradients in particular regions.…”
Section: Determinants Of A-diversitysupporting
confidence: 88%
“…In addition, this second analysis shows that isolation is a question of neighborhood scale. While we have shown that small habitat fragments tend to have less rich species pools (perennials) than equivalent portions of continuous habitat, it seems that increasing the (reachable) amount of habitat in their neighborhood effectively increases this richness (Akatov, Chefranov, & Akatova, ; Pärtel & Zobel, ; Schamp, Laird, & Aarssen, ). This seems consistent with the hypothesis that the matrix surrounding habitat fragments is more permeable than water, especially for perennial plants (e.g., Butaye, Jacquemyn, Honnay, & Hermy, ).…”
Section: Discussionmentioning
confidence: 92%
“…Bruun, 2000;Cousins and Eriksson, 2002;Öster et al, 2007). However, it has been recognized that plant community structure and diversity may also be affected by neighbouring habitats via effects on the regional species pool and dispersal limitations (Akatov et al, 2005;Pärtel et al, 1996;Söderström et al, 2001;Zobel, 1997). It is supposed that the habitats surrounding certain plant communities represent sources of species which are not regular components of the given community, as their ecological optima lie in another vegetation type, but which can survive under suboptimal conditions (accessory or satellite species).…”
Section: Introductionmentioning
confidence: 99%